Valorization of Wastes from Wine Industry in the Production of Lightweight Clay Bricks - José Matos; André Cruz; Luís Marques; Rui Pereira (U.Porto Journal of Engineering)
Lightweight clay brick is an idea that arose from the need to reduce waste by giving grape pomace, a waste product from the Portuguese wine sector, a new use, promoting a circular economy. Compared to ordinary building clay bricks, lightweight clay bricks have higher porosity, and consequently lower density and lower thermal conductivity, while maintaining good mechanical strength, allowing them to be used to build the inner walls in buildings. The production process for this brick, from obtaining the raw materials to manufacturing the brick itself, was studied using process simulation and an economic analysis. The latter led to the conclusion that the project is economically viable and profitable, with each tonne of bricks selling for €57.96.